Perioperative systematization for the prevention of hematomas following face-lift procedures: a personal approach based on 1,138 surgical cases - Ticiano Cesar Teixeira Cló; Walter Ferraz Flávio; Carlos Eduardo Guimarães Leão; Felipe Xavier Cló; Leonardo Mourão Lacerda; Luiza Ramos Leão (Revista Brasileira de Cirurgia Plástica)
Introduction: Hematoma, the most frequent complication of face-lift procedures, may require a second surgical approach, which delays patient recovery. In the literature, its incidence ranges from 0.2% to 8%, and further studies are essential to standardize preventive measures. The objective is to present a proposal of perioperative systematization for effectively prevention of hematoma formation after rhytidectomies. Methods: We analyzed the medical records of 594 patients who underwent operation by the author between 2011 and 2018 to compare the incidence of hematomas before and after the systematization implemented in 2015. Results: From July 2011 to December 2014, before the adoption of the systematization, the incidence of hematomas was 3.43% in 233 cases. After its adoption, the incidence decreased to 1.66% in 361 cases. The last 177 consecutive cases did not have this complication. Conclusion: We observed a significant reduction in the incidence of hematomas following rhytidectomy after the use of the proposed standardization. None of the measures would be effective alone; thus, their combined adoption is essential in preventing this serious complication.